STRUKTUR DAN NILAI DIDAKTIS PADA PUISI BERTEMA “BELAJAR DARING” KARYA SISWA KELAS X DI SMKS UNGGULAN HUSADA BANJARMASIN (STRUCTURE AND DIDACTIC VALUE IN THE THEMED POETRY OF “ONLINE LEARNING” BY CLASS X STUDENTS AT SMKS UNGGULAN HUSADA BANJARMASIN) - Rusma Noortyani (Universitas Lambung Mangkurat, 2021)
Structure and Didactic Value in the Themed Poetry of “Online Learning” by Class X Students at SMKS Unggulan Husada Banjarmasin. The purpose of this study was to describe the structure of poetry by class X-B students at SMKS Unggulan Husada Banjarmasin and to examine the didactic value of poetry by class X-B students at SMKS Unggulan Husada Banjarmasin. Data collection was carried out from May 30 to June 30, 2021 through an online form of poetry writing performance test. The data analyzed were 18 pieces of poetry. The data collection procedures in this study were reading, identifying, codifying, and classifying according to the research focus. Data analysis uses deep meaning understanding techniques. Checking the validity of the data is done through triangulation techniques. The results of the study found that the structure that builds a poem consists of a physical structure and an inner structure. The physical structure consists of typography, rhyme, images, figure of speech, concrete words, and diction. The inner structure consists of theme, tone, and atmosphere. After analyzing the poems by class X-B students of FKK Vocational High School Husada Banjarmasin, it was found that the poems contained the entire physical and mental structure. The didactic values contained in the poem are in the form of moral and religious didactic values. Keywords: structure, didactic values, poetry, online learning, student work Abstrak Struktur dan Nilai Didaktis pada Puisi Bertema “Belajar Daring” Karya Siswa Kelas X di SMKS Unggulan Husada Banjarmasin. Tujuan penelitian ini untuk mendeskripsikan struktur puisi karya siswa kelas X-B SMKS Unggulan Husada Banjarmasin dan mengkaji nilai didaktis dari puisi karya siswa kelas X-B SMKS Unggulan Husada Banjarmasin. Pengumpulan data dilaksanakan 30 Mei-30 Juni 2021 melalui daring berupa tes unjuk kerja menulis puisi. Data yang dianalisis berjumlah 18 buah puisi. Prosedur pengumpulan data dalam penelitian ini adalah membaca, mengidentifikasi, mengodifikasi, dan mengklasifikasikan sesuai dengan fokus penelitian. Analisis data menggunakan teknik pemahaman arti secara mendalam. Pengecekan keabsahan data dilakukan melalui teknik triangulasi. Hasil penelitian ditemukan struktur yang membangun sebuah puisi terdiri atas struktur fisik dan struktur batin. Struktur fisik terdiri atas tipografi, rima, imaji, majas, kata konkret, dandiksi. Struktur batin terdiri atas tema, nada, dan suasana. Setelah dilakukan analisis pada puisi karya siswa kelas X-B FKK SMKS Unggulan Husada Banjarmasin diperoleh bahwa puisi-puisi tersebut memuat keseluruhan struktur fisik dan batin. Nilai didaktis yang terdapat dalam puisi tersebut berupa nilai didaktis moral dan agama. Kata-kata kunci: struktur, nilai didaktis, puisi, belajar daring, karya siswa